Registration of Wheat Lines Carrying the Partial Stripe Rust Resistance Gene Yr36 without the Gpc‐B1 Allele for High Grain Protein Content. Issue 1 (4th October 2012) - Hale, I.; Zhang, X.; Fu, D.; Dubcovsky, J.
Abstract : While the high‐temperature adult‐plant resistance gene Yr36 represents a promising source of quantitative and potentially race‐nonspecific resistance to wheat stripe rust (causal organism Puccinia striiformis Westend. f. sp. tritici ), its tight linkage (0.3 cM) with the high grain protein content (GPC) gene Gpc‐B1 may hinder its introgression in certain cases, such as in soft wheat varieties requiring low GPC or in lines where the Gpc‐B1 allele may be associated with a yield penalty. The development and registration of two donor lines, one tetraploid ( Triticum turgidum L. ssp. durum ; Reg. No. GP‐945, PI 656793) and one hexaploid ( T. aestivum L. ssp. aestivum ; Reg. No. GP‐946, PI 664549), each carrying the resistant wild emmer ( T. turgidum ssp. dicoccoides ) allele for Yr36 linked with the nonfunctional Gpc‐B1 allele, are intended to overcome this potential limitation. Meiotic recombination events breaking the linkage between these two genes were discovered during the systematic screening of a population of 4500 F2 durum plants ('Langdon' background) used to fine map Yr36 . One of the critical recombination events was selected for fixation by self‐pollination and transferred to a California‐adapted spring hexaploid background (breeding line UC11105+10 ) through five generations of backcrossing. Genotypic and phenotypic data confirm the presence of Yr36 and the nonfunctional Gpc‐B1 allele in both registered lines.